Application Research of Low-density Polypropylene Materials on Door Trim Panels. Issue 1 (1st January 2023) - Li, Shupeng; Li, Bo
Abstract: Lightweight design is an important indicator in the process of automobile development, including product structure design, using plastic instead of steel and low density materials and other technical solution, this paper studies low density material technology to achieve lightweight automotive parts. The material system of polypropylene (PP)/elastomer/talc blends(PP+EPDM-TD)was selected to study the combination of different types of PP (homopolymer PP and random PP) and talc powder (mesh number and content) in the material formula. With the goal of the performance of the door panel parts, PP materials with 5% (PP+EPDM-TD5), 10% (PP+EPDM-TD10) and 20% (PP+EPDM-TD20) talc content were developed to verify the material properties. 10% and 20% talc content can meet the requirements. Then, the two materials were comprehensively evaluated from the aspects of parts forming analysis, size verification and application cost, and the low-density material (PP+EPDM-TD10) was finally selected for application to meet the lightweight design requirements of parts.